2020
DOI: 10.1002/ajim.23159
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Thoroughbred horse farm workers’ compensation insurance claims in Kentucky: Injury frequency, cost, lost time, and associated occupational factors

Abstract: Background Thoroughbred horse farm workers self‐report a high frequency of work‐related injuries and pain. However, an analysis of Thoroughbred horse farm workers’ compensation injury claims is absent from the literature, yet may benefit worker safety. Methods We analyzed workers’ compensation insurance firm data containing 2276 claims filed between 2008 and 2015. Injury frequency, cost, and lost time per cause, nature, and body part injured were examined qualitatively and via univariate tests. Factors associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Many studies have used workers′ compensation FROI in the context of injury cause and monetary impact 18–20 . However, no known study has used worker′s compensation FROI data to assess occupational injury in the distillery industry.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have used workers′ compensation FROI in the context of injury cause and monetary impact 18–20 . However, no known study has used worker′s compensation FROI data to assess occupational injury in the distillery industry.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, there are no previous reports of work‐related injury among distillery workers in the literature. However, other studies have sought to examine the frequency of injury, cost of injury, lost time, task performed before injury, and percent of disability through the use of workers′ compensation data 16–20 . Such studies were conducted to identify factors associated with occupational injuries, determine the subsequent monetary and physical consequences, and put forth recommendations for prevention.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a Swedish study (1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014), Meredith et al [4] gave a conservative calculation of 3.2 million Euro annually of 1800 Euro per injury event. A USA study which analyzed thoroughbred horse farm workers' compensation insurance claims (2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015) found that the total amount paid on claims were USD $11,181,268 and the total number of lost-time days was 18,412 [5]. When analyzing the costs for treatment at a USA Level 1 Trauma Centre for the period of 2010-2013, Adler et al [6] calculated the mean expenditure per injured patient at USD $29,737 with the total expenditure for all the patients (N = 222) more than USD $6.5 million.…”
Section: Introductionmentioning
confidence: 99%
“…Heinrich’s triangle theory [ 15 ], as refined by Bird [ 16 ], postulates that there is a numerical relationship between near misses (i.e., events that could have resulted in an injury in different circumstances) and minor and major injuries, with the incidence of near-misses and minor injuries being significantly higher than that of major and fatal injuries. Several studies worldwide have identified the equine sector as a high-risk work environment [ 17 , 18 , 19 , 20 , 21 ]. Despite this, research focusing on the work environment and safety in the equine sector is limited.…”
Section: Introductionmentioning
confidence: 99%